Impact of Health Education on the Knowledge and Practice of 3rd Grade Guidance School Girls of Shahrbaback in Relation to Mensturation Health in 2003 - Zahra Jalili; Sakineh Mohammad alizadeh; Soraya Atta-ollahi (Kerman University of Medical Sciences, 2004)
Background: Adolescence is accompanied with deep psychological physiological and social changes Girls lack of awareness about this period could form the basis of many physical and behavioral problems Planned health education programs carried out to develop required skills and abilities leave clear impression on the manner the youth handles these changes Objective: The aim of this study was determining the impact of health education on the knowledge and practice of 3rd grade guidance school girls of Shahrbabak city (Kerman/Iran) in relation to the health of menstruation Methods: The present study is a quasi experimental (beforeafter) in which 200 Subjects were chosen by multistage random sampling method Data collection was carried out through a questionnaire containing 23 questions divided into two parts of knowledge and practice After determining the validity and reliability questionnaires were distributed among subjects (pretest) Final testing (posttest) was administered after training courses Results: Findings of the pre test stage represented weak knowledge and practice of the students concerning health of menstruation and there was significant increase in mean scores of knowledge [from 58 (414%) to 127 (907%)] and practice [from 237 (658%) to 283 (786%)] after training program (P